Introduction: Quotas, Parties and Electoral Design – Mechanisms and Effects of Ethnic Representation in Diverse Societies. Issue 3 (3rd July 2022) - Tan, Netina
ABSTRACT: This article introduces the special issue and places the eight contributions in context. It offers a discussion of the key terms and highlights the contributions of the articles for forging new research agendas on ethnic inclusion and political representation. Drawing from cases from the Asia Pacific, Americas and Europe, this special collection of papers investigates the effects and practices of electoral designs on the descriptive and substantive effects of ethnic minority representation based on both qualitative and quantitative methods. Together, the findings seek to engender debate and advance contemporary scholarship on comparative democratisation, electoral and party politics and conflict resolution studies on indigenous and ethnic minority representation.